Contradictory distributive principles and land tenure govern benefit-sharing of payments for ecosystem services (PES) in Chiapas, Mexico. (1st May 2022) - Izquierdo-Tort, Santiago; Corbera, Esteve; Martin, Adrian; Lillo, Julia Carabias; Dupras, Jérôme
Abstract: Payments for Ecosystem Services (PES) are incentive-based instruments that provide conditional economic incentives for natural resources management. Research has shown that when economic incentives are parachuted into rural communities, participation and benefits are collectively negotiated and shared. However, we know little about how benefit-sharing evolves over time in community-based PES. To address this gap, we examine distributional justice in four communities of the state of Chiapas, Mexico, which participate in a PES programme, and we assess how local justice principles compare with the programme's goals. Our analysis reveals patterns of both continuity and change in how communities share PES benefits, which reflect a suite of contradictory justice principles, including entitlement, merit, need, and equality. The studied communities distribute PES benefits by providing differentiated compensation to diverse groups of landholders via private cash payments, whilst also attending non-landed community members through public infrastructure investments. We show that benefit-sharing is strongly influenced by pre-existing land tenure features and associated norms, which in the study area include three different types of individual and common-property. Yet, we also show that communities continuously adjust benefit-sharing arrangements to navigate distributional challenges emerging from programme engagement. Overall, we provide novel insights on the evolution, diversity, and complexity of distributive justice in community-based PES and we advocate for a context-sensitive, nuanced, and dynamic account of justice in incentive-based conservation.